Some Inequalities under Random C- Condition (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this paper, the notion of random nonexpansive operators  is generalized to operators satisfying random  condition. Some new properties are obtained in uniformly convex Banach spaces, also well we get result of converge on random operator to random point in Banach space.